DESAIN MODEL PERKULIAHAN TARGHIB-TARHIB DALAM PENDIDIKAN AGAMA ISLAM - Yahya, M. Wildan Bin H. M. (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstract. This article tries to explain the advantages and stages of lectures with the targhib-tarhib model. This model is proven to have an instructional impact, namely as a religious motivator and increasing religious obedience. In addition, it has an accompanying impact, namely scientific research skills and fosters curiosity (curiosity) as to why Allah has decreed a command and a prohibition. The stages of teaching begin by outlining the natural punishment for sinners and natural rewards for those who are religiously obedient; followed by reading, translating, and explaining the verses of the Koran about targhib-tarhib; then discuss the message of targhib-tarhib verses; continued again by describing the misery of the hereafter for sinners and happiness for religious people; and finally asked the students to express their message and attitude towards the whole message of the Qur'an about the targhib-tarhib. Keywords: PAI teaching model, targhib-tarhib, natural punishments, ukhrawi punishments Abstrak. Artikel ini berusaha memaparkan keunggulan dan tahap-tahap perkuliahan dengan model targhib-tarhib. Model ini terbukti memiliki dampak instruksional, yakni sebagai motivator beragama dan meningkatkan ketaatan beragama. Selain itu memiliki dampak penyerta, yakni ketrampilan riset ilmiah dan menumbuhkan curiosity (rasa ingin tahu) mengapa Allah menetapkan suatu perintah dan larangan. Adapun tahap-tahap pengajaran dimulai dengan menguraikan hukuman alamiah terhadap pelaku dosa dan ganjaran alamiah bagi orang yang taat beragama; dilanjutkan dengan membacakan, menterjemahkan, dan menjelaskan ayat-ayat Al-Quran tentang targhib-tarhib; kemudian mendiskusikan pesan ayat-ayat targhib-tarhib; dilanjutkan lagi dengan menggambarkan kesengsaraan akhirat bagi pelaku dosa dan kebahagiaan bagi orang yang taat beragama; dan terakhir meminta siswa/mahaiswa untuk mengungkapkan pesan dan sikapnya terhadap keseluruhan pesan Al-Quran tentang targhib-tarhib itu. Kata kunci: Model mengajar PAI, targhib-tarhib, hukuman-ganjaran alamiah, hukuman-                ganjaran ukhrawi